EKSISTENSI PERTUNJUKAN WAYANG KULIT TANTRI SEBAGAI KAJIAN ESTETIKA - I Putu Ardiyasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
One of the forms of Balinese culture is wayang as a medium of worship and communication. Wayang Tantri as one of the genres of wayang performances in Bali lived on the art stage in the year - + 1982. This article contains information about the spiritual dimension related to the aesthetic dimension in Wayang Tantri, so as to preserve the existence on the screen of the elderly. This study uses data collection consisting of interviews and documentation. The data in this study are in the form of narrative description with data analysis techniques using descriptive analysis. Showing shows, the Wayang Tantri show is a puppet creation that began processing since the early 1980s. Using structures that rotate traditional Balinese Wayang Kulit (Parwa and Ramayana). The basis for cultivating Tantri puppets is the Balinese traditional wayang, plays, forms of puppets, and accompaniment. With different forms of puppets, the game techniques are different. This is as a form of reading the development of the puppet audience community that is more recent technological developments.Keywords: Existence, Aesthetics, Wayang Tantri